Transcriptome of Aquilaria malaccensis containing agarwood formed naturally and induced artificially - Farah Adibah Abdul Kadir; Kamalrul Azlan Azizan; Roohaida Othman (BMC Research Notes, 2021)
Abstract Objectives Agarwood is the aromatic heartwood formed upon wounding of Aquilaria trees either naturally formed due to physical wound sustained from natural phenomena followed by microbial infection, or artificially induced using different inoculation methods. Different induction methods produce agarwoods with different aromas which have impacts on their commercial values. In lieu of elucidating the molecular mechanisms of agarwood formation under different treatment conditions, the transcriptome profiles of trunk tissues from healthy A. malaccensis tree, and naturally and artificially induced trees were obtained. Data description The transcriptome of trunk tissues from healthy A. malaccensis, and naturally and artificially induced trees were sequenced using Illumina HiSeq™ 4000 platform which resulted in a total of 38.4 Gb clean reads with Q30 rate of at least 91%. The transcriptome consists of 85,986 unigenes containing 1305 bases on average which were annotated against several databases. From this, 44,654 unigenes were mapped to 290 metabolic pathways in the Kyoto Encyclopedia of Genes and Genomes database. These transcriptome data represent considerable contribution towards Aquilaria transcriptome data and enhance current knowledge in comprehending the molecular mechanisms underlying agarwood formation in Aquilaria spp.